Comparing outcomes of concurrent chemotherapy regimens in patients 65 years old or older with locally advanced oropharyngeal carcinoma. Issue 22 (6th October 2018) - Amini, Arya; Eguchi, Megan; Jones, Bernard L.; Stokes, William A.; Gupta, Abhinav; McDermott, Jessica D.; Massarelli, Erminia; Bradley, Cathy J.; Karam, Sana D.
Abstract : Background: The comparative efficacy of cisplatin (CDDP), carboplatin, and cetuximab (CTX) delivered concurrently with radiation for locally advanced oropharyngeal squamous cell carcinoma continues to be evaluated. Methods: The linked Surveillance, Epidemiology, and End Results–Medicare database was used to identify and compare patient and disease profiles, mortality, toxicity, and overall cost for patients with oropharynx cancer undergoing definitive concurrent chemoradiation with CDDP, carboplatin, or CTX between 2006 and 2011. The human papillomavirus status was unknown. The primary outcome was 2‐year overall survival (OS). Results: Four hundred nine patients receiving concurrent CDDP (n = 167), carboplatin (n = 69), or CTX (n = 173) were included. Those who were older, those who were nonwhite, and those with a Charlson Comorbidity Index ≥ 2 were less likely to receive CDDP. Two‐year OS was inferior with CTX (hazard ratio [HR], 1.68; 95% confidence interval [CI], 1.08‐2.60; P = .020) and no different with carboplatin (HR, 1.31; 95% CI, 0.73‐2.35; P = .362) in a Cox proportional hazards model (reference CDDP). There was no statistically significant difference between carboplatin and CTX (HR, 1.28; 95% CI, 0.77‐2.14; P = .891). Rates of antiemetic use and hospital visits for nausea/emesis/diarrhea or dehydration were statistically higher with CDDP. Pneumonia rates were higher with carboplatin. In the multivariate model, the corrected mean per‐patient spending was significantly higher for CTX and carboplatin than CDDP ($61, 133 and $65, 721 vs $48, 709). Conclusions: Patients who received CDDP had improved OS. CDDP was also associated with slightly lower overall costs and higher antiemetic usage and hospital visit rates, although a strong selection bias was observed because those receiving CTX and carboplatin were older and had higher comorbidity scores. Abstract : Cisplatin is associated with improved overall survival, slightly lower overall costs, and higher antiemetic usage and hospital visit rates. Concurrent cisplatin may be the favored chemotherapy agent, with carboplatin‐ or cetuximab‐based therapy reserved for those who otherwise cannot tolerate concurrent cisplatin for locally advanced oropharynx cancer.